Exploring Allophones and Minimal Pairs of Vowels and Consonants In English Phonology - Lubis, Yani; Hasyanah, Hafifah; S, Shafirahasan; Maharani, Widya; Fadhilah, Raudhotul (Madani: Jurnal Ilmiah Multidisiplin, 2024)
In pronouncing words correctly, people should consider the sound system inherent in a particular language. Studying pronunciation is essential for enhancing students' language abilities in English. It holds a significant position in English instruction. According to Candlin and Chrichton, pronunciation is not only necessary for speaking but also for effective communication and conveying meaning in a clear and comprehensible manner. In other words, when a speaker communicates a message, it should be received by the listener with clarity and understanding. However, there are instances where the listener may not comprehend or appear perplexed by what the speaker has said. The research encompasses the researcher's strategy for data collection and analysis. According to research design refers to the researcher's plan for proceeding within the specific context of the study. In this research, a descriptive study with a qualitative approach was employed. Qualitative research aims to describe phenomena using words as the primary means of analysis. as for the conclusion of the discussion These minimal pairs are important for illustrating the distinct vowel phonemes in the English language and their role in conveying meaning. and help explain sound variations, sound changes, and sound distribution patterns in the language. By studying phonological rules, we can understand the principles underlying the sound system of language and how it sounds-these sounds interact in different linguistic contexts.